Geographic Information System for Mapping Vegetable Producing Areas in West Bandung Regency complete with maps and travel routes - Anggun Nugroho; Joko Santoso; Wayan Karang Utama; Ni Luh Putri Srinadi (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2022)
This study develops a system that provides information about the location of producing vegetables and fruit and the route to the selected location in the form of a map in the form of a GIS system. This research was conducted to support the Department of Agriculture and Food Security of West Bandung Regency (KBB), which does not yet have such a system. Information about agriculture and food crops is still in the form of news and simple and there is no map feature, let alone a route feature to the location of producing vegetables and fruit. Making this web using the PHP programming language, MySQL database, CSS, HTML, Google Maps API. Information on vegetable and fruit producers was obtained from the Department of Agriculture and Food Security of the KBB. The map was taken from Google Maps, then edited to provide information on producing vegetables and fruit and travel routes to the selected location. The results of this study are a Geographic Information System which is displayed in the form of a website equipped with features in the form of information on the location of vegetables and fruit producers, news, articles, visitor comments, maps and routes to vegetables and fruit producers. These maps and routes have been adapted to the actual conditions to be passed by web visitors or fruit and vegetable commodity seekers in West Bandung district. The location of this object was obtained by conducting a direct survey to the object of agriculture and vegetable and fruit producing plantations. By implementing features from the Google Maps API that utilize the Auto Update function and Directions Service to display maps in mapping the location of agricultural commodities for this geographic information system, visitors can find out the locations of agricultural commodities in West Bandung district without having to ask other peoples. Website administrators can add new vegetable and fruit producing locations or change or delete. From the results of the questionnaire, it was found that the geographic information system for mapping agricultural products in West Bandung district has been running and functioning well with a satisfaction level of 76.92%.